Strategi Komunikasi Organisasi Kepala Madrasah Dalam Meningkatkan Kinerja Guru di MI Mumtaza Islamic School, Pondok Cabe Tangerang Selatan. - Ahmad Quraisy Sa'id; Dessy Andamisari (LUGAS Jurnal Komunikasi, 2025)
This study aims to examine the organizational communication strategies implemented by the head of the madrasah in improving teacher performance at MI Mumtaza Islamic School, South Tangerang. Using a qualitative exploratory approach, the research focuses on vertical and horizontal communication patterns, including organizational communication barriers and their solutions. Data collection techniques include in-depth interviews, participant observation, and documentation. The findings reveal that the madrasah head implements participatory, spiritually grounded, and adaptive two-way communication strategies. Vertical communication is realized through daily briefings, formal instructions, and evaluation forums. Horizontal communication takes place through teacher collaboration, routine discussions, and digital media platforms. Challenges include understanding gaps, limited digital literacy, and resistance to change. Solutions include capacity building in digital tools, open communication forums, and continuous feedback systems. These strategies have contributed to improved teacher performance in five main dimensions: quality, quantity, attendance, punctuality, and teamwork. This study contributes conceptually to strengthening organizational communication in Islamic educational institutions.